Implementation of Green Campus-Based Curriculum Model at Islamic Universities in Indonesia - Jaya, Indra (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
This study is aimed to investigate the implementation of green campus-based curriculum model at Islamic universities in Indonesia. In depth interview was conducted to the top leader of universities in order to confirm the application of green campus-based curriculum especially on vision and mission. A set of interviews was also questioned to lecturers to obtain important information regarding with the employment of the model of curriculum related to environmental health they used in classrooms. In addition, supporting data about students from lecturers’ information was also occupied to enrich the data. As a result, the researcher found that all Islamic universities observed in this study imply green campus or environmental aspect points in university’s vision and mission. Less than 100% of lecturers are able to design learning materials related to environmental health as well as implementing it in classrooms. Less than 60% of students can produce environmental work arts as well as having problem solving skills toward surrounding environment. Above all, hose Islamic universities determine similar goals on green campus-based curriculum model i.e. to preserve the environment and aware of surrounding natural issues. At the end, a few suggestions were suggested to the top manager of the Islamic universities concerning with vital element regarding with lecturers’ competencies in developing environmental health learning design that should be noticed and increased.